2019
DOI: 10.1016/j.ygcen.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth status using endocrine growth indices, insulin-like growth factor (IGF)-I and IGF-binding protein-1b, in out-migrating juvenile chum salmon

Abstract: This study aimed to utilize circulating insulin-like growth factor binding protein (IGFBP)-1b as a negative index of growth to evaluate the growth status of juvenile chum salmon (Oncorhynchus keta) in the ocean. First, rearing experiments using PIT-tagged juveniles were conducted to examine the relationship of circulating IGFBP-1b with growth rate of the fish in May and in June. The serum IGFBP-1b level negatively correlated with fish growth rate in both months, suggesting its utility as a negative index of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In several fishes, including salmonids, endocrine IGF-I is valuable as a growth index because its circulating level generally correlates with individual growth rate (Beckman et al 2004a, b;Picha et al 2008;Beckman 2011). The validity of serum IGF-I as a growth index has been confirmed for juvenile chum salmon, and the juvenile growth status in the coastal area of the Abashiri region, eastern Hokkaido, has been evaluated (Kaneko et al 2015(Kaneko et al , 2019Taniyama et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In several fishes, including salmonids, endocrine IGF-I is valuable as a growth index because its circulating level generally correlates with individual growth rate (Beckman et al 2004a, b;Picha et al 2008;Beckman 2011). The validity of serum IGF-I as a growth index has been confirmed for juvenile chum salmon, and the juvenile growth status in the coastal area of the Abashiri region, eastern Hokkaido, has been evaluated (Kaneko et al 2015(Kaneko et al , 2019Taniyama et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed a radioimmunoassay (RIA) and a time-resolved fluoroimmunoassay (TR-FIA) for salmon IGFBP-1b and showed that circulating IGFBP-1b increased in fasting fish and negatively correlated with individual growth rates in immature coho salmon (Onocorhynchus kisutch), masu salmon (O. masou), and chum salmon (O. keta) (18,29,30,44,45). These findings led us to propose its utility as a quantitative negative index of growth.…”
Section: Introductionmentioning
confidence: 99%